Sequencing of Phospholipase and Enterotoxin Genes of B. Fragilis Isolated from Women with BV - Zahraa Kais Salman (Journal of Global Pharma Technology, 2018)
One of the most common genital infections among women in the childbearing age is Bacterial vaginosis (BV). Many novel, fastidious and uncultivated bacterial species are related with BV. These are called bacterial vaginosis associated bacteria (BVAB), present in trace amount and have a significant role in the infection. A total of 300 high vaginal swabs were obtained from 150 non-pregnant women with bacterial vaginosis depending on Amsel criteria. Two swabs where taken for each patient, 150 of these swabs were cultivated on selective media, Bacteroides Bile Esculin agar and the remaining samples were used for direct DNA detection. Samples were collected from a patient who’s admitted to the out-patient clinics of Gynecology and Obstetrics in Babylon Maternity and Pediatrics teaching hospital Hospital, and Al-Hillah General Teaching Hospital. Cultivated swabs were gave 31(21%) positive results for Gram negative, anaerobic Bacteroides fragilis.  Specific primers used for detection and study  two of virulence factors .The direct molecular detection revealed 39 (26 %)  of sample positive for detection by nan H  gene where gave band with a molecular weight of (842 bp) and all of these samples where revealed 39 (100 %) positive result for enterotoxin gene and 35 (89.7%) of them gave positive result for phospholipase gene, by produced  (367 bp) PCR prodcut    for amplification of enterotoxin gene and (400 bp) PCR product for amplification of phospholipase gene. Sequencing of enter toxin and phospholipase genes gave similar identity in percentages (100 and 99) respectively with the standard strains in NCBI web site.Keywords: Bacterial vaginosis, Selective media, Molecular detection, PCR-technique, Sequencing.